2009
DOI: 10.1080/01480540903130641
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide (NO), citrulline–NO cycle enzymes, glutamine synthetase, and oxidative status in kainic acid–mediated excitotoxicity in rat brain

Abstract: Neuronal excitation, involving the excitatory glutamate receptors, is recognized as an important underlying mechanism in neurodegenerative disorders. To understand their role in excitotoxicity, the nitric oxide synthase (NOS), argininosuccinate synthetase (AS), argininosuccinate lyase (AL), glutamine synthetase (GS), and arginase activities, along with the concentration of nitrate/nitrite, thiobarbituric acid-reactive substances (TBARS), and total antioxidant status (TAS), were estimated in the cerebral cortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 41 publications
4
18
0
Order By: Relevance
“…In this context the cellular damage seems to be directly correlated to cellular ROS concentration. Usually, cells are able to cope with ROS through different protective mechanisms that prevent the generation of reactive species, or remove them before they can fatally damage cells [25]. The main target of free radicals are lipids, nucleic acids, carbohydrates and proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In this context the cellular damage seems to be directly correlated to cellular ROS concentration. Usually, cells are able to cope with ROS through different protective mechanisms that prevent the generation of reactive species, or remove them before they can fatally damage cells [25]. The main target of free radicals are lipids, nucleic acids, carbohydrates and proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Epileptic form activity was shown to cause excessive production of ROS/RNS, a factor believed to be involved in the mechanisms leading to neurodegeneration and cell death (Itoh and Watanabe, 2009). The increased production of NO and increased oxidative stress in kainic acid mediated excitotoxicity and epilepsy has been reported earlier (Swamy et al, 2009(Swamy et al, , 2011a.…”
Section: Discussionmentioning
confidence: 99%
“…It was earlier reported that GS becomes nitrated and inhibited during PTZ induced seizure model at repeated PTZ seizure induction, but there was no decrease in GS protein level (Bidmon et al, 2008). Our earlier studies demonstrated that increased production of NO, increased activity of NOS, decreased activity of GS and increased oxidative stress in KA mediated excitotoxicity (Swamy et al, 2009(Swamy et al, , 2011a. Therefore the present study was conducted to assess the neuroprotective effects of the bee product propolis , by estimating the glutamine synthetase activity, nitric oxide (NO), thiobarbituric acid reactive substances (TBARS) concentration and total antioxidant status (TAS) in cerebral cortex (CC), cerebellum (CB) and brain stem (BS) of rats supplemented with propolis and subjected to KA mediated excitotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Propolis has been shown to have broad biological activities, which are principally attributed to the presence of flavonoids (major component; rutin, quercetin, galangin, etc. ), phenolic compounds and CAPE (Isla et Our earlier studies have shown that NOS and NO were increased along with increased oxidative stress markers in KA mediated excitotoxicity and epilepsy rat models (Swamy, et al, 2009(Swamy, et al, , 2011a. We have also reported the amelioration of oxidative stress and NO concentration by propolis suplimentation in KA mediated excitotoxicity .…”
Section: Swamy Et Al Afr J Tradit Complement Altern Med (2014) 11(5)mentioning
confidence: 99%